The Implementation Process Assessment Tool: translation, contextualization, and psychometric evaluation of a Swedish version in a municipal elderly care context - Monica Kaltenbrunner; Heidi Hagerman; Cecilia Fagerström; Miriam Hartveit; Espen Nordheim; Mirjam Ekstedt (BMC, 2024)
Abstract Background The number of older adults with complex healthcare needs is growing alongside limited resources available in health services. To meet this challenge, it is urgent that healthcare staff are motivated and able to continuously translate new knowledge and working methods into daily practice. To facilitate such implementation, supportive measures responding to the healthcare personnel's needs seem essential. The present study aims to translate, contextualize and test a Swedish version of the Implementation Process Assessment Tool (IPAT) for measuring the facilitation needs among staff implementing a new working process in municipal elderly care. Methods A mixed-method design was used. First, the existing instrument was translated into Swedish. Thereafter, twelve staff members with different professions working in healthcare and at the municipal elderly care were interviewed using Think-aloud interviews to contextualize and test the face validity of the translated instrument. Lastly, the adjusted instrument (Swe-IPAT) was psychometrically evaluated through a cross-sectional survey among 305 staff members working in municipal elderly care. Results The psychometric evaluation of the Swe-IPAT revealed satisfying properties. Three factors, largely in line with the original IPAT, are suggested. Internal consistency assessed using Cronbach's alpha was 0.93 for the factor individual phases for behavioral change and perception of the intervention, 0.84 for the factor individual activities, and 0.95 for the factor collective readiness and support. Conclusions The 27-item Swe-IPAT, translated into Swedish and contextualized, demonstrated satisfactory psychometric properties when tested in an elderly care context. The instrument is suggested to be useful in providing feedback to managers in tailoring support and assessing implementation efforts among healthcare staff in elderly care. However, more research is needed to evaluate its properties throughout the entire implementation process and to test the usability of Swe-IPAT in other settings.